Higher‐Order Assessment in Gross Anatomy: A Comparison of Performance on Higher‐ Versus Lower‐Order Anatomy Questions between Undergraduate and First‐Year Medical Students. Issue 3 (23rd December 2020) - Thompson, Andrew R.; Giffin, Bruce F.
Abstract : Gross anatomy is considered by many the backbone of medical education. While learning anatomy has a reputation of requiring mainly rote memorization, modern day anatomy education often involves instruction and assessment at cognitive levels that foster higher‐order thinking. In many instances, these higher‐order anatomical concepts are taught to graduate students in healthcare‐related fields, such as medicine. At this level, students are expected to apply and analyze anatomical information since that is what will ultimately be expected of them as professionals. In contrast, undergraduate anatomy education is typically more introductory in nature and often takes place in the setting of a large‐enrollment course that serves as a prerequisite for many health sciences degree programs. In this study, variables related to the assessment of higher‐order concepts in clinical anatomy were compared between first‐year medical students and undergraduate students enrolled in an upper‐level human gross anatomy course. Results demonstrate that undergraduate students perform lower than medical students overall, but the degree of difference in how they perform on higher‐ versus lower‐order questions is comparable. The most notable exception is on practical examinations, where undergraduate students tend to struggle more with applying and analyzing information. Exploration of additional variables provides insight into how the cognitive level being assessed affects the time it takes to answer a question and how different practical examination question types and formats influence student performance. Findings presented in this study have implications for designing anatomy courses and underscore the importance of blueprinting assessments.